Tertiary lake sedimentation in the Elko Formation, Nevada -- the evolution of a small lake system in an extensional setting - Horner, William H., author; Egenhoff, Sven O., advisor; Harry, Dennis, committee member; von Fischer, Joe, committee member; Amerman, Robert, committee member (Colorado State University. Libraries, 2015)
The Lower to Middle Eocene Elko Formation of northeastern Nevada consists of basal coarse-grained siliciclastics and carbonates which are overlain by an organic-rich succession consisting of fine-grained siliciclastics, in places with fine-grained carbonates, and fine- to coarse-grained volcaniclastics at the top. Based on lithological and sedimentological characteristics in four documented localities arranged along a north-south transect, the succession shows fourteen facies, which are grouped into five facies associations (FAs): Siliciclastic mudstones and conglomerates (FA1); Massive coal-rich mudstones (FA2); Microbial-mat-bearing mudstones and carbonates (FA3); Microbial-mat-bearing mudstones and volcaniclastics (FA4); Carbonates and volcaniclastics (FA5). The succession is interpreted to reflect deposition in a broad continental-lacustrine setting. FA1 rocks record sedimentation in the most proximal environment, consisting of alluvial-fluvial sedimentation. FA2 rocks reflect deposition in a marginal low-energy swamp environment, while FA3 rocks denote "open-water" lacustrine sedimentation in a limnetic setting that was highly sensitive to lake-level fluctuations. FA4 rocks record the onset of extrabasinal airfall tuff in the limnetic portion of the lake, and FA5 rocks record volcaniclastic sedimentation outpacing subsidence in the lake, ultimately "filling" up available accommodation space and ending lacustrine sedimentation. The studied succession is subdivided into four vaguely chronostratigraphic intervals referred to as Stratigraphic Intervals 1 to 4, which record a lake system with significant lateral changes in accommodation space and resulting facies patterns in a north to south progression through time. Based on two recent 40Ar/39Ar dates and four previous radiometric age dates, the northern outcrop, which is significantly older than the central and southern ones, records initial subsidence and the onset of lake sedimentation (Stratigraphic Interval 1). Subsidence varied over time causing the lacustrine depocenter and limnetic depozone to progressively shift southwards (Stratigraphic Intervals 2 through 4). Black shale source rocks in the measured sections therefore occur along the entire north-south transect of the studied lacustrine system, yet they represent rocks of different ages not correlatable throughout the Elko Formation. Coeval volcanism, which led to increased volcaniclastic sediment supply, followed black shale deposition and contributed to the north-south "filling in" of the lake system, ultimately culminating with the end of lacustrine sedimentation around 37.5 Ma. The Elko Formation black shales have high source rock potential as an unconventional resource play, as their organic content consists almost entirely of Type-I (oil prone) kerogen. Contrary to deep-water, thermally-stratified anoxic-lake source rock models, long considered to be the only environments in which significant organic-matter preservation may have occurred, this study provides evidence for black shale deposition in the Elko lake to have occurred within a "shallow," mostly oxic environment in the photic zone. Further, this research indicates that depositional environments in lacustrine settings may be scale-dependent. The Elko Formation is not merely a scaled-down version of large-lake systems, such as that in which the Green River Formation formed, but a unique type of system with its own set of controls. With increased industry attention being placed on this potential lacustrine petroleum system, this study provides a new source rock model, as well as a temporal and spatial framework to be used as a predictive tool for the identification of rich source rock intervals in the Elko Basin.